Wayside School beneath the Cloud of Doom - Sachar, Louis, 1954- (Sachar, Louis, 1954- Wayside School series., 2020)
Follows the adventures and misadventures of students and staff as they cope with the effects of a large, gloomy cloud that has settled over Wayside School.